EVALUATION AND MOLECULAR DETECTION OF ADVANCED INBRED LINES FOR QPM STATUS IN MAIZE (ZEA MAYS L.) - D. LENKA; P. N. JAGADEV; D. SWAIN; P. KANUNGO; DEVIDUTTA LENKA; I. C. MOHANTY; SWAPAN K. TRIPATHY (The Bioscan, 2020)
A set of 20 advanced inbred lines of maize derived from diverse source populations (CIMMYT, Hyderabad Centre, India and DMR, New Delhi, India), were evaluated for fifteen agro-morphological traits including seed yield. VL1016548 and VL1016453 revealed high yield potential (50 q/ha) as also in case of QPM-11-7-1, QPM-8-3-2 and VL109273. Interestingly, QPM 8-3-2 with medium height plant type and maturing within 97 days, managed to have high yield potential (51.25 q/ha). VL1017524 recorded maximum cob length (17.2 cm) and number of kernels per row (37.1) and 100-kernel weight (32.7gm), but yielded moderately low owing to lower number of kernel rows/cob, total number of kernels/cob and shelling percentage. Cluster analysis based on molecular profiling revealed two highly divergent mono-genotypic clusters containing VL1016548 and VL1017524 respectively and a third cluster with rest 18 inbred lines together. The QPM allele specific marker phi 057 revealed more discriminating power (Rp=1.8) among the genotypes compared to umc 1066(Rp=1.2). Among the selected 20 inbreds, QPM11-7-1, QPM 7-3-2, QPM 8-3-2, QPM 10-13-1, VL1016414, VL109476, VL109475, VL1016399, VL1017054, VL109412 and VL1016590 revealed the 169bp QPM allele following PCR with phi 057 and hence, these may be considered as potential QPM inbred lines. These inbred lines may serve as valuable material for QPM breeding.